(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
In French as a Foreign Language class in Nigeria where the Nigerian learners of the language study the language against the background of their mother tongue/ English Language which they have attained to some level a reasonable degree of competence, the making of errors is inevitable since the learners concerned are faced with a lot of linguistic problems such as; interference of their Native tongue/English on French language and other linguistic problems emanating from French language. The study is set to take a look into the role of Contrastive Analysis/ Error Analysis in solving French learners’ error problems.